Effect of Glueline Shape on Strength of Mortise and Tenon Joint - Silvana Prekrat (University of Zagreb, Faculty of Forestry and Wood Technology, 2010)
Tenon joints are widely used in constructions of skeletal furniture and numerous laboratory experiments were conducted with the aim of determining the rigidity and strength of such joints. In industrial practice, the sloppily applied glue often covers only flat, rectangular planes of the tenon. In this situation, it can be intuitively predicted that such joints are characterised by low strength but the precise assessment of this difference, requires carrying out appropriate experiments and numerical calculations. Therefore, the aim of the performed investigations was: to define the strength of a tenon joint in the construction of a chair with a connecting piece, to determine the distribution of shear and normal stresses in the glue bond and to ascertain the infl uence of the glueline on this strength. The finite element mesh for the tenon joint was developed by using orthotropic, 20-node block elements, whereas the glue bond was modelled using isotropic elements 0.1 mm thick. The performed investigations showed that the shape of the glueline exerts a strong influence on the strength of the tenon joint. The pressure of the tenon on the mortise via the layer of the glue bond changes the form of deformations. Non-dilatational deformations, which generate shear stresses of values exceeding the ultimate strength, develop in rectangular bonds, whereas in superellipse bonds non-dilatational deformations clearly restrict the pressure of the tenon on the mortise and, by doing so, decrease considerably the level of dangerous shear stresses.